2011
DOI: 10.1016/s2212-4268(11)60005-5
|View full text |Cite
|
Sign up to set email alerts
|

A study of morphological patterns of lip prints in relation to gender of North Indian population

Abstract: Background: Establishing a person's identity is a very important process in civil and criminal cases. Dental, fingerprint and DNA comparisons are probably the most common techniques allowing fast and secure identification processes. However, in certain circumstances related to the scene of the crime or due to lack of experienced personnel, these techniques might be unavailable; so there is still an increasing need for reliable alternative methods of establishing identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 7 publications
0
28
0
2
Order By: Relevance
“…From that moment on, the lip groove patterns rarely change, resisting many afflictions and hence lip prints aid as a tool in human identification. [23]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From that moment on, the lip groove patterns rarely change, resisting many afflictions and hence lip prints aid as a tool in human identification. [23]…”
Section: Introductionmentioning
confidence: 99%
“…[23] However, very few studies have been conducted using lip prints for population identification. In India, some studies have shown that the patterns formed reveal a population-wise dominance, that is, a particular population will show predominance of a particular lip print type.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to sex, lip prints vary from males and females in the given age group and no similarity was seen between any compartments. 4 In a Study on 50 male and 50 female subjects of Kerala origin on Lip Print Types, Type IV most frequently observed in both the sexes and in both the quadrants. 5 Our findings are consistent with this study.…”
Section: Discussionmentioning
confidence: 96%
“…Grooves on lips appear as early as 6 th weak of intrauterine life & once appeared their pattern do not change. 4 YasuoTsuchihashi conducted a study on lip print patterns of Japanese people and the lip prints classified in to six types. 5 Type I:Clear-cut grooves running vertically across the lip Type I': The grooves are straight but disappear half-way instead of covering the entire breadth of lip.…”
Section: Introductionmentioning
confidence: 99%
“…In males, Type II pattern was the most predominant in both lips followed by Type III and Type V on the upper lip, and Type IV and Type I pattern on the lower lip. Gupta et al [17] reported that the intersected type of pattern was the most commonly seen pattern in females and the branched type of pattern in males. Reticular pattern (Type IV) was the least common type of pattern in both males and females.…”
Section: Discussionmentioning
confidence: 99%